Kadar Zat Besi, Vitamin C dan Daya Terima Nugget Ikan Bandeng Berbasis Tepung Daun Kelor untuk Pengecahan Anemia: Iron Levels, Vitamin C and Acceptability Tests of Milkfish Nugget Based on Moringa Leaf Flour for Anemia Prevention - Hiqma, Nurul; Nurulfuadi; Ariani,; Mappiratu, Kurniawati (Poltekkes Kemenkes Palu, 2024)
Background: Anemia is a condition characterized by reduced hemoglobin in the body. As a result, the organs of the body do not get enough oxygen, making people with anemia pale and easily tired. The cause of anemia is due to low consumption of food sources of iron and there are substances that can inhibit iron absorption in food. Consuming iron sources, especially heme iron and iron enhancers can increase iron absorption thereby reducing the risk of anemia. Purpose:. This study aims to analyze iron levels, vitamin C and acceptability in milkfish nugget formulations based on moringa leaf flour. Methods: This study used a quasi-experimental method with a Complete Randomized Design (RAL) research design, with 5 levels of treatment 2 repetitions (Duplo). Analysis of iron and vitamin C levels using UV-Vis Spectrophotometry method. Analysis of iron levels using the Kruskal Wallis test, analysis of vitamin C levels using the One Way Anova test and statistical tests used on acceptability using the Kruskal Wallis test. Results: The results showed the highest iron (fe) levels found in F4 of 4.97 mg / 100g, the highest vitamin C levels found in F4 of 8.71 mg / 100g and could meet the needs of iron RDA of 22.5% and vitamin C of 9.6%. The results of the F1 acceptability test are the most accepted formulas in terms of color, aroma, texture and taste with the criteria of somewhat like. Conclusion: There is no significant difference in iron and vitamin C with a p value of > 0.05, and the acceptability of milkfish nuggets based on Moringa leaf flour there is a significant difference between formulas with p values of < 0.05 and F1 is the most preferred formula with a substitution of Moringa leaf flour as much as 25%.